2007
DOI: 10.1016/j.joca.2006.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dutch version of the Hip disability and Osteoarthritis Outcome Score

Abstract: The Dutch HOOS questionnaire has a good internal consistency and reliability. Moreover, the construct validity is good and no floor and ceiling effects were found. The HOOS is a good instrument for patients with different stadia of hip OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 17 publications
5
115
2
3
Order By: Relevance
“…For the selection of activities, an expert group in the field of OA (i.e., physical therapists, a rehabilitation physician, an orthopedic surgeon, a rheumatologist, [human movement] scientists, and patient research partners) used the following sources: the ICF core set for hip and knee OA (18), items in existing self-reported questionnaires (19,20), performance-based tests (21,22), and self-reported activity limitations (by using the Patient-Specific Complaints Questionnaire) (23) collected from 400 patients in the Amsterdam Osteoarthritis (AMS-OA) cohort in an outpatient center for rehabilitation and rheumatology (Reade, Amsterdam, The Netherlands) (24).…”
Section: Significance and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the selection of activities, an expert group in the field of OA (i.e., physical therapists, a rehabilitation physician, an orthopedic surgeon, a rheumatologist, [human movement] scientists, and patient research partners) used the following sources: the ICF core set for hip and knee OA (18), items in existing self-reported questionnaires (19,20), performance-based tests (21,22), and self-reported activity limitations (by using the Patient-Specific Complaints Questionnaire) (23) collected from 400 patients in the Amsterdam Osteoarthritis (AMS-OA) cohort in an outpatient center for rehabilitation and rheumatology (Reade, Amsterdam, The Netherlands) (24).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…The focus group consisted of men and women with hip OA-and knee OA-related complaints. The average age was 65 years (range 47-80 years), the average H/KOOS function, activities of daily living (ADL) subscale score was 49 (range 28 -79; 0 -100 scale, where 0 ϭ worst and 100 ϭ best) (19,20,25), and the mean numerical rating scale (NRS) for pain was 4.6 (range 2-8; 0 -10 scale, where 0 ϭ best and 10 ϭ worst). The European League Against Rheumatism recommendations for inclusion of patients in research projects were adopted (26).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…The HOOS consists of 40 items divided into five subscales: pain, other symptoms, function in daily living, function in sports and recreation, and hip-related quality of life. 5 The items are scored on a 5-point Likert scale. For each subscale, the raw score is transformed to a 100-point score.…”
Section: Region-specific Questionnairesmentioning
confidence: 99%
“…Numerous disease-specific or region-specific patientreported questionnaires are used for this purpose. [2][3][4][5][6] However, when one wishes to evaluate and compare outcome amongst different groups of patients or patients with multiple injuries, these questionnaires are not suitable. The Short Musculoskeletal Function Assessment (SMFA) was therefore developed by Swiontkowski et al 7 The SMFA is a patient-reported questionnaire, designed to detect differences in functional status of patients who have a broad range of musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Our quality intervention was centered on the so-called Mother Nature factor (patient intrinsic characteristics) and in particular on the importance of patient's expectations in influencing their rating of the ''process performance.'' The selection of patient expectations as a potential predictor of outcome was based on both a literature review [e.g., [50][51][52][53], previous studies conducted in our department, and on the feedback of the spine surgeons regarding their own impression of why patients might be disappointed with their results following what might be viewed by the surgeons as a successful operation [54]; one important characteristic of the 6-r is that it is based on an effective teamwork, where the opinions of all individuals involved in the process are taken into account.…”
Section: Definementioning
confidence: 99%